(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The relationship between the State and the Regions that characterizes the management of the pandemic has recorded many moments of “conflict” in the school, especially during the resumption of the school year after the Christmas break. It has included the regional courts (TAR) which in various regions (Campania, Puglia, Calabria, Basilicata, Emilia Romagna, Lombardia) have tried to indicate a way able to unravel the tangle of rules. Perhaps different instruments are needed in the confrontation between the State and the Regions while we ask ourselves if the sacrifice of the right to education imposed by many governors is entirely justified.